Mudando o olhar: a criança ensina seus pais a serem pais - reflexões sobre o atendimento da criança com sua família - Duque, Francisly Munck (2019)
The practice of assisting children and their families offers single challenges to the therapist’s performance. Trying to understand the children’s necessities and engaging the members of the system in the process are some of the familiar therapist’s concerns. This research objective is to comprehend children and their families’ psychotherapy, in which the infant is capable of expressing his/her necessities to parents and able to analyze how it is, for parents, to go through this experience. A qualitative research was developed from a systemic/ constructivist theoretical approach. Reports of a child and his family’s concluded psychological care were used as instruments, a semi-structed interview was realized with the infant’s parents seven years after the psychotherapy experience. Statements of other two cases were also used in this research. The qualitative techniques of content analysis show that the care format in weekly appointments with the child allows a proximity which helps the therapist go deep in the child’s issues. The monthly appointments with the family revealed important moments of reflection for all involved, clarifying suffering causes as well as opinions of family events. The infant speech may be understood in his/her expression of play, in a variety of techniques, individual and familiar. It’s intended, in this research, to cooperate for a reflection upon the practice of assisting children and their families, benefiting therapists’ performances, discussing practices and making room for other researches